How sweet is too sweet? Measuring sweet taste preferences and liking in familiar and unfamiliar foods amongst Dutch consumers - E.M. Čad; C.S. Tang; M. Mars; K.M. Appleton; K. de Graaf (Food Quality and Preference, 2023)

Predictors and Outcomes of Neurological Deterioration in Intracerebral Hemorrhage: Results from the TICH-2 Randomized Controlled Trial - Zhe Kang Law; Rob Dineen; Timothy J England; Lesley Cala; Amit K Mistri; Jason P Appleton; Serefnur Ozturk; Daniel Bereczki; Alfonso Ciccone; Philip M Bath; Nikola Sprigg (Translational Stroke Research, 2021)
Neurological deterioration is common after intracerebral hemorrhage (ICH). We aimed to identify the predictors and effects of neurological deterioration and whether tranexamic acid reduced the risk of neurological deterioration. Data from the Tranexamic acid in IntraCerebral Hemorrhage-2 (TICH-2) randomized controlled trial were analyzed. Neurological deterioration was defined as an increase in National Institutes of Health Stroke Scale (NIHSS) of ≥ 4 or a decline in Glasgow Coma Scale of ≥ 2. Neurological deterioration was considered to be early if it started ≤ 48 h and late if commenced between 48 h and 7 days after onset. Logistic regression was used to identify predictors and effects of neurological deterioration and the effect of tranexamic acid on neurological deterioration. Of 2325 patients, 735 (31.7%) had neurological deterioration: 590 (80.3%) occurred early and 145 (19.7%) late. Predictors of early neurological deterioration included recruitment from the UK, previous ICH, higher admission systolic blood pressure, higher NIHSS, shorter onset-to-CT time, larger baseline hematoma, intraventricular hemorrhage, subarachnoid extension and antiplatelet therapy. Older age, male sex, higher NIHSS, previous ICH and larger baseline hematoma predicted late neurological deterioration. Neurological deterioration was independently associated with a modified Rankin Scale of > 3 (aOR 4.98, 3.70–6.70; p < 0.001). Tranexamic acid reduced the risk of early (aOR 0.79, 0.63–0.99; p = 0.041) but not late neurological deterioration (aOR 0.76, 0.52–1.11; p = 0.15). Larger hematoma size, intraventricular and subarachnoid extension increased the risk of neurological deterioration. Neurological deterioration increased the risk of death and dependency at day 90. Tranexamic acid reduced the risk of early neurological deterioration and warrants further investigation in ICH. URL: https://www.isrctn.com Unique identifier: ISRCTN93732214

Thermal profiling for parallel on-line monitoring of biomass growth in miniature stirred bioreactors - N. K. Gill; M. Appleton; G. J. Lye (Biotechnology Letters, 2008)